A multi‐mode wideband omnidirectional monopolar patch antenna for indoor wireless communication systems. Issue 9 (22nd June 2017) - Liu, Le; Cai, Yuan‐Ming; Zhao, Luyu; Yin, Yingzeng; Hu, Wei
Abstract: A wideband omnidirectional monopolar patch antenna merged multi‐mode with a simple structure is proposed in this article. The antenna consists of a circular patch and a concentric annular ring, which is coupled‐fed by a T‐shape monopole at its center. A wideband performance is achieved by converging multi‐mode: TM02 mode of the circular patch, TM02 mode of the annular ring and monopole mode of the T‐shape monopole. The measured results show that the proposed antenna has an impedance bandwidth of 55.3% from 4.45GHz to 7.85GHz. All of the three resonant modes lead to conical radiation patterns in the elevation plane and omnidirectional radiation patterns in the azimuth plane, and the measured peak gain varies from 6.1 to 10 dBi within the operating band, which verifies it can be a good choice for indoor wireless communication systems.